2007
DOI: 10.1038/sj.npp.1301420
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cocaine and MDMA Self-Administration on Serotonin Transporter Availability in Monkeys

Abstract: Although serotonin (5-HT) can interact with dopamine (DA) systems to modulate the subjective and reinforcing effects of psychostimulants such as cocaine and 3,4-methyldioxymethamphetamine (MDMA, ecstasy), the long-term effects of exposure to psychostimulants on brain 5-HT systems are not well characterized. The present study assessed 5-HT transporter (SERT) availability using positron emission tomography (PET) in rhesus monkeys with the SERT-specific radioligand [11 C]3-amino-4-(2-dimethylaminomethyl-phenylsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 60 publications
(76 reference statements)
4
46
5
Order By: Relevance
“…In contrast, experimenter-administered low doses of MDMA (1.5 mg/kg×3) did not significantly modify basal or drugstimulated levels of DA or 5-HT in the striatum of rats (Baumann et al 2008). Similarly, using operant protocols, two studies in monkeys show no deficits in SERT following a prolonged self-administration of small amounts of MDMA (0.33 mg/kg/day; Fantegrossi et al 2004;Banks et al 2008). However, with respect to mice, no evidence relating alterations in DA markers with repeated selfadministration of MDMA has been put forward.…”
Section: Discussionmentioning
confidence: 77%
“…In contrast, experimenter-administered low doses of MDMA (1.5 mg/kg×3) did not significantly modify basal or drugstimulated levels of DA or 5-HT in the striatum of rats (Baumann et al 2008). Similarly, using operant protocols, two studies in monkeys show no deficits in SERT following a prolonged self-administration of small amounts of MDMA (0.33 mg/kg/day; Fantegrossi et al 2004;Banks et al 2008). However, with respect to mice, no evidence relating alterations in DA markers with repeated selfadministration of MDMA has been put forward.…”
Section: Discussionmentioning
confidence: 77%
“…Increases in the SERT after chronic cocaine have been reported in cells (Kittler et al, 2010), rodents (Cunningham et al, 1992), nonhuman primates (Banks et al, 2008;Gould et al, 2011), and humans (Jacobsen et al, 2000;Mash et al, 2000). Chronic self-administration of cocaine in rhesus monkeys also resulted in an upregulation of 5-HT 2A R in the frontal cortex (Sawyer et al, 2012) as determined in vivo with PET imaging and the selective 5-HT 2A R ligand [ 11 C]M100907 (Fig.…”
Section: Cortical Dysregulation and 5-ht 2a/c Receptor Functionmentioning
confidence: 99%
“…Two studies in monkeys have examined the effects of self-administered MDMA on indices of central 5-HT function [30,34] . Neither of these, however, found that self-administered MDMA produced significant decreases in 5-HT, although a trend was observed in 1 study [30] .…”
Section: Effects Of Repeated Exposure To Mdmamentioning
confidence: 99%